The Impact Of Parental Divorce On Children's Rights According To The Perspective Of Islamic Law Through The Maqoshid Syariah Approach (Study Of Decision Number 2560/Pdt. G/2022/Pa. Bks ) - Indah Choiriyah; Musyaffa Amin Ash Shabah; Suprihatin; Agus Supriyanto (Muwafaqat: Journal of Islamic Law, 2025)
This thesis aims to find out the basis of the Panel of Judges' considerations in the Decision of the Bekasi Religious Court Number 2560/Pdt.G/2022/PA.Bks in the Divorce Lawsuit for the accumulation of hadlonah and child support, and to find out the basis of Islamic Law in this decision.This research aims to analyze the impact of parental divorce on children's rights based on an Islamic legal perspective using the Maqashid Syariah approach, with a case study of Decision Number 2560/Pdt.G/2022/PA.Bks. Maqashid Syariah are principles in Islamic law that aim to protect five basic human interests: religion, soul, reason, lineage and property. In this context, research focuses on how the protection of children's rights, including rights to custody, education, living and psychological well-being, is considered and applied in divorce decisions. The research method used is a qualitative approach with juridical-normative analysis of Decision Number 2560/Pdt.G/2022/PA.Bks. Data was obtained through studying court decision documents and literature related to Islamic law and Maqashid Syariah. The analysis was carried out by examining how Maqashid Syariah principles were applied in the decision to ensure the protection and welfare of children.The research results show that in this decision, the court decided that child care was under the responsibility of the mother, while the father was obliged to provide maintenance. This decision is based on Maqashid Syariah principles which emphasize the importance of protecting the lives and welfare of children. Apart from that, this decision also takes into account the psychological aspects of the child to reduce the negative impact of divorce